Competências gerenciais de professores-gestores do ensino superior: um estudo comparativo entre coordenadores de instituições públicas e privadas de Belo Horizonte (MG) - Ana Paula Costa Oliveira (2018)
This study has as general objective to Analyze and compare the managerial competences (ideal-required and real-effective) of coordinators from public and private highereducation institutions in Belo Horizonte (MG), in their own perception, based on the Quinn et al. (2003) model. In the theoretical framework, the managerial role, the managerial work and the academic-managers role at the higher-education institutions were approached, as well as the professional competences, the managerial competences, the Quinn et al. (2003) model, the academic-managers managerial competences and the competences of the course coordinator of higher-education institutions. In order to answer the research problem, the methodological procedures are supported by a descriptive field research, through a survey, and also by quantitative and qualitative researches, characterizing a methodological triangulation that propiciates greater depth and range to the research. The data coming from the Quinn et al. (2003) quantitative questionnaire was processed from the univariate and bivariate statistic analysis, and the responses to the open-ended questions were submitted to content analysis. The results show the requirement to a balanced and satisfactory action in all the roles, in both parties, with emphasis on the higher predominance of the roles of mentor, facilitator and monitor on coordinators from public institutions and the higher predominance of the roles of mentor, facilitator, director, innovator and producer on coordinators from private institutions. In terms of the findings of their effective performance, the coordinators of public institutions have real-effective competences related to the roles of mentor and facilitator, while the ones from private institutions have competences tied to the roles of mentor, facilitator, director, innovator and producer. Regarding the process of acquisition and development of the managerial competences, it was noticed that the coordinators from private institutions develop themselves through courses, dialog, studies and the performance of a higher number of formation/refreshment activities, while the coordinators from public institutions develop themselves only through practicing the everyday management, not having any incentive relating the actions of formation, training and refreshing. Lastly, against all these findings, the study limitations are cited, its contributions are pointed and the recommendations for future researches are formulated.